Prevalence and determinants of psychological insulin resistance among type 2 diabetic patients in Kinshasa, Democratic Republic of Congo - Shomba L. Rita; Fina J.-P. Lubaki; Lepira F. Bompeka; Gboyega A. Ogunbanjo; Lukanu P. Ngwala (AOSIS, 2019)
Background: Psychological insulin resistance (PIR) is a common but unappreciated phenomenon by health care providers with a negative impact on the control of type 2 diabetes mellitus. Aim: To determine the frequency of PIR and its determinants in patients with type 2 diabetes. Setting: This study was conducted in Kinshasa in three health centres providing management of diabetic patients. Methods: This study was a multicentric, cross-sectional study conducted from 01 November 2017 to 31 March 2018 in Kinshasa among 213 type 2 diabetic patients who were taking oral anti-diabetic drugs. A standardised questionnaire, the Chinese Attitudes to Starting Insulin Questionnaire (Ch-ASIQ), was used for data collection. Results: The average age of participants was 59.8 ± 11.1 years with a male to female ratio of 1.5. The prevalence of PIR was 42.7%; and its main determinants were 50 years of age (odds ratios [OR] adjusted 2.05; 95% confidence interval [CI] 1.98-4.27; p = 0.045), the presence of complications (OR adjusted 3.33; 95% CI 1.68-6.60; p = 0.001), lack of knowledge about insulin therapy (OR adjusted 1.96; 95% CI 1.03-3.71; p = 0.040) and the high cost of insulin (OR adjusted 2.32; 95% CI 1.08-4.95; p = 0.030). Conclusion: The study showed that almost half of type 2 diabetic patients had PIR with the main determinant factors related to the patient and the health system. The establishment of a therapeutic education programme, improved 'provider-patient' communication and the development of approaches to increase access to drugs are crucial to reduce the prevalence of PIR.